2010
DOI: 10.1073/pnas.0912066107
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical, multilayered cell walls reinforced by recycled silk cocoons enhance the structural integrity of honeybee combs

Abstract: We reveal the sophisticated and hierarchical structure of honeybee combs and measure the elastic properties of fresh and old natural honeycombs at different scales by optical microscope, environmental scanning electron microscope, nano/microindentation, and by tension and shear tests. We demonstrate that the comb walls are continuously strengthened and stiffened without becoming fragile by the addition of thin wax layers reinforced by recycled silk cocoons reminiscent of modern fiber-reinforced composite lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…We believe this mechanism may also be responsible for the hexagonal cell pattern in natural honeycombs. 33 …”
Section: B Minimization Of the Surface Energy At The Macroscale Or Omentioning
confidence: 99%
“…We believe this mechanism may also be responsible for the hexagonal cell pattern in natural honeycombs. 33 …”
Section: B Minimization Of the Surface Energy At The Macroscale Or Omentioning
confidence: 99%
“…The deformations of honeycombs are approximately classified into two major groups: stretchingdominated behaviour or bending-dominated behaviour [11,12]. For instance, the honeycombs packed by hexagonal cells, which are typically observed in nature [13], belong to the group of bending-dominated structures and have some useful and interesting mechanical properties: for example, high capacity for energy absorption [14,15], and multiple buckling shapes and post-buckling behaviour [16,17]. Conversely, triangular cells, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of honeybees, just before pupation, the larvae cover the waxen walls of their cells with silk (Huber 1814;Arnhart 1906), paying out the fibres randomly so that, by the end of the spinning, the walls are covered by thin sheets of silk in which the individual fibrils are readily discernible (Jay 1964;Zhang et al 2010a). Jay (1964) observed that fibres were formed when the honeybee spinneret was drawn away from the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…Late final instar honeybee larvae were induced to spin silk within plastic tubes and the clean silk removed before the larvae added any further material (with kind permission of the publishers from Sutherland et al 2011b). composite (Hepburn and Kurstjens 1988;Zhang et al 2010a). The physical significance of these observations can be illustrated by comparing the properties of the native fibroin, wax-free sheets of silk, silk-free wax, propolis and the final wax-silk composite (Kurstjens et al 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation